Pattern of Partnership between Simbo Hydroponic Business and CV. Family Garden Mart - Shavira, Kifra; Bafadal, Azhar; Yusria, Wa Ode (International journal of technology and education research, 2025)
This study aims to analyze the pattern of partnership, benefits and commitments between Simbo Hydroponic Business and CV. Family Garden Mart. The method used is a case study with a qualitative and quantitative descriptive approach. Data were obtained through interviews and questionnaire dissemination using the Likert scale. The withdrawal of informants was carried out purposively on both parties who have established partnerships since 2019. Data analysis uses reduction, data presentation and conclusion drawing for the qualitative aspect, as well as the assessment of average scores for the quantitative aspect. The results of the study show that the partnership pattern applied is a contractual partnership, because the distributor does not provide capital, all costs are borne by the farmer himself, while the company acts as an offtaker that absorbs the crop consistently. From the results of the quantitative analysis, the benefits of partnerships according to Simbo Hydroponic Business are in the very good category (score 4.66), including market certainty, table prices and increased revenue. Meanwhile, according to CV. Family Garden Mart in the good category (score 4.6) partnership provides a guarantee of quality vegeTabel supply, supply continuity, and strengthening of market position. The partnership commitment was rated 4.8 very well by farmers, reflected in the discipline in delivery and product quality while CV. Family Garden Mart of 4.5 shows commitment through regular purchasing schedules, on-time payments, and open communication.